Reduction in Ocular Hypotensive Eyedrops by Ab Interno Trabeculotomy Improves Not Only Ocular Surface Condition But Also Quality of Vision - Kenji Kashiwagi; Mio Matsubara (Journal of Ophthalmology)
Purpose. To investigate the effect of ab interno trabeculotomy using the Trabectome surgical system on tear film stability and functional visual acuity (FVA). Patients and Methods. Adult glaucoma patients who underwent Trabectome surgery alone or Trabectome surgery combined with phacoemulsification with intraocular lens insertion were included in this study. Corneal epithelial defects, tear film breakup time (TBUT), tear meniscus height, tear film spreading grade, tear interferometry grade, and FVA were assessed before and after surgery in addition to routine ophthalmic examinations. Changes in ocular surface conditions and visual acuity as a result of the Trabectome surgery were investigated. Results. Thirty eyes of 22 patients with a mean age of 72.2 ± 7.9 years, including 8 males and 14 females, were enrolled. The Trabectome surgery significantly reduced the intraocular pressure (IOP) from 20.3 ± 5.2 to 15.0 ± 3.3 mmHg (P<0.001) and the number of different types of ocular hypotensive eyedrops used from 3.2 ± 0.7 to 1.1 ± 0.7 types (P<0.001). The surgery significantly improved corneal epithelial defects, the tear spreading grade, the tear interferometry grade, and FVA. The surgery also improved the visual maintenance ratio among all enrolled patients, including those who underwent Trabectome surgery only. Conclusion. Trabectome surgery may be beneficial not only for IOP reduction but also for improving ocular surface conditions and FVA.